Criminal Responsibility for Recruiting Women into Terrorist Organizations - Mohammad Abd ALNomani, Maitham; Tram Al-Nawfali, Shaima; Hatem Toman Birmani, Aseel (International Journal of Psychosocial Rehabilitation, 2020)
The phenomenon of the recruitment of women into terrorist organizations has become dangerous in terms of the effects arising from them in order to use these organizations for modern technological means with the difficulty of monitoring and tracking, in addition to the security and legislative challenges to combat this new type of terrorism, as the recruitment of women has received great approval among terrorist organizations. They made it their deadly weapon in the implementation of terrorist attacks in various parts of the world, especially in Iraq and Syria, at the lowest cost and with the least possible effort, so they relied on traditional and technological means to recruit them to terrorist groups to implement the terrorist program, taking advantage of the most important segment of society, which poses the seriousness of this phenomenon, which requires confronting them by all means.